2004
DOI: 10.1182/blood-2004-04-1558
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the AID protein in normal and neoplastic B cells

Abstract: IntroductionSomatic hypermutation (SHM) is a specialized process that takes place in germinal center (GC) B cells in response to T celldependent antigen stimulation. 1,2 This process introduces single nucleotide substitutions, with occasional deletions and duplications, primarily into the variable region of the immunoglobulin (IgV) heavy and light chain genes, resulting in the production of high-affinity antibodies and allowing affinity maturation of the humoral immune response. 3 SHM requires active transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
145
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(161 citation statements)
references
References 50 publications
14
145
0
2
Order By: Relevance
“…This sounds contradictory; however, Bombardieri et al 25 reported that neoplastic marginal zone-like B cells are AID-negative but have somatic and ongoing mutations. 26 On the other hand, Smit et al, 27 Pasqualucci et al 28 and Lossos et al 9 reported of lack of correlation between AID expression and intraclonal diversity of VH genes in B-cell non-Hodgkin's lymphomas. And Smit et al 27 mentioned that AID expression at follicular lymphomas were 25%, and intraclonal variation was found in the absence of AID, but they did not explained histology, immunophenotype and stage.…”
Section: Duodenal Follicular Lymphomamentioning
confidence: 99%
“…This sounds contradictory; however, Bombardieri et al 25 reported that neoplastic marginal zone-like B cells are AID-negative but have somatic and ongoing mutations. 26 On the other hand, Smit et al, 27 Pasqualucci et al 28 and Lossos et al 9 reported of lack of correlation between AID expression and intraclonal diversity of VH genes in B-cell non-Hodgkin's lymphomas. And Smit et al 27 mentioned that AID expression at follicular lymphomas were 25%, and intraclonal variation was found in the absence of AID, but they did not explained histology, immunophenotype and stage.…”
Section: Duodenal Follicular Lymphomamentioning
confidence: 99%
“…One important aspect of this GC program is AID, which mediates somatic hypermutation and IG CSR in normal GC cells but in experimental settings can also induce IG/MYC translocations similar to those found in BL (Pasqualucci et al 2004;Ramiro et al 2004). GC-restricted transcription factors can have a powerful oncogenic effect when dysregulated because they can simultaneously affect multiple downstream pathways.…”
Section: The Role Of the Germinal Center Reaction In The Development mentioning
confidence: 99%
“…The difference with AID-GFP, which accumulates in the nucleus of Ramos, could be explained by a combination of overexpression and the C-terminal tag weakening retention, just as an N-terminal tag affects import. AID is vastly confined to the cytoplasm of germinal center B cells 48,[53][54][55] . Only a very small proportion of the B cells in rabbit appendix 48 and human tonsils 53 , and hardly any cell in unsynchronized populations overexpressing AID-GFP, seem to contain predominantly nuclear AID.…”
Section: Functional Implicationsmentioning
confidence: 99%